Complex organizations : A Sociological Perspective - Haas, J. Eugene; Drabek,Thomas E. (New York, 1973)
We begin the book with a brief statement about the nature of logical theory. We believe (at least most of the time) that en research directed at the testing and clarification of theory can a cumulative body of knowledge applicable under specified con In the long run, theory that has been empirically verified t scientific research methods will prove more valuable to administrators and other practitioners than prescriptive statements about how organizaions "ought" to behave under all conditions.
Keywords: Social psychology